2016
DOI: 10.1021/acs.chemmater.5b05006
|View full text |Cite
|
Sign up to set email alerts
|

Design and Epitaxial Growth of MoSe2–NiSe Vertical Heteronanostructures with Electronic Modulation for Enhanced Hydrogen Evolution Reaction

Abstract: Transition metal dichalcogenides (MX2, where M = Mo or W and X = S or Se) have been regarded as some of the best alternatives for noble metal-free electrocatalysts for the hydrogen evolution reaction (HER). A tremendous number of attempts have mainly focused on the maximization of the number of active edge sites and the conductivity of MX2-based electrocatalysts to enhance HER performance. However, for MX2-based electrocatalysts, the acceleration of the kinetic process to improve HER performance has been negle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 315 publications
(259 citation statements)
references
References 57 publications
9
245
1
Order By: Relevance
“…The onset potential of CoTeNR/NF reaches −126 mV (vs RHE) and only requires the low overpotential of 202 mV to derive 10 mA cm −2 , while the NiTeNR/NF and bare NF need 248 and 371 mV overpotential to derive 10 mA cm −2 , respectively. Although the HER activity of CoTeNR/NF catalyst is still slightly inferior to commercial 20% Pt/C under alkaline conditions, it is among forefront of the most reported transitional metal‐based HER catalysts at current density of 10 mA cm −2 , e. g., Co 0.85 Se 2 /NiFe‐LDH/G (260 mV), MoSe‐NiSe (210 mV), Ni 2 P/NF (220 mV), NiCo 2 S 4 NW/NF(210 mV), Ni 3 S 2 (220 mV) and CoP nanowires (209 mV), etc (Table S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…The onset potential of CoTeNR/NF reaches −126 mV (vs RHE) and only requires the low overpotential of 202 mV to derive 10 mA cm −2 , while the NiTeNR/NF and bare NF need 248 and 371 mV overpotential to derive 10 mA cm −2 , respectively. Although the HER activity of CoTeNR/NF catalyst is still slightly inferior to commercial 20% Pt/C under alkaline conditions, it is among forefront of the most reported transitional metal‐based HER catalysts at current density of 10 mA cm −2 , e. g., Co 0.85 Se 2 /NiFe‐LDH/G (260 mV), MoSe‐NiSe (210 mV), Ni 2 P/NF (220 mV), NiCo 2 S 4 NW/NF(210 mV), Ni 3 S 2 (220 mV) and CoP nanowires (209 mV), etc (Table S2, Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…From Figure d, one can see that both Ni 3d orbitals and Se 4p orbitals crossing the E F . This may be caused by the performance of metallic properties of NiSe 2 . Under the light irradiation, the photo‐induced electrons would transfer from the S 3p orbitals to the Cd 5s orbitals along the Ni 3d orbitals or Se 4p orbitals, which act as electron transport “high speed railways” to accelerate the migration of electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the pure Ni 0.85 Se, we notably found that the diffraction peaks of iron-doped nickel selenides were shifted to higher angles, which may be owing to the substitution of Fe for Ni. 26,27 As exhibited in Figure 2c, the Fe 2p spectrum indicates that there are two binding energy peaks at 706.1 and 712.2 eV, which correspond to Fe 2+ 2p 3/2 and Fe 3+ 2p 3/2 , respectively. For the Ni 2p spectrum (Figure 2b), the peak located at 852.4 eV with its satellite peak at 855.5 and 861.1 eV originates from Ni 2p 3/2 , while the peak at 869.7 eV with its satellite peak at 873.2 and 879.1 eV is assigned to Ni 2p 1/2 .…”
Section: Structural Characterizationsmentioning
confidence: 92%